Berberine Protects Against Simulated Ischemia/Reperfusion Injury-Induced H9C2 Cardiomyocytes Apoptosis In Vitro and Myocardial Ischemia/Reperfusion-Induced Apoptosis In Vivo by Regulating the Mitophagy-Mediated HIF-1α/BNIP3 Pathway - Na Zhu; Jiang Li; Yongli Li; Yuwei Zhang; Qiubo Du; Peiyuan Hao; Jinying Li; Xueming Cao; Li Li (Frontiers Media S.A., 2020)
Berberine (BBR) has a variety of pharmacological activities and is widely used in Asian countries. However, the clinical application of BBR still lacks scientific basis, what protective mechanism of BBR against myocardial ischemia-reperfusion injury (MIRI). In vitro experiments, BBR pretreatment regulated autophagy-related protein expression, induced cell proliferation and autophagosome formation, and reduced the mitochondrial membrane potential (ΔΨm) increase in H9C2 cells. In vivo experiments, BBR reduced the myocardial infarct size, decreased cardiomyocyte apoptosis, and markedly decreased myocardial enzyme (CK-MB, LDH, and AST) activity-induced I/R. In addition, upon BNIP3 knockdown, the regulatory effects of BBR on the above indicators were weakened both in H9C2 cells and in vivo. Luciferase reporter and ChIP assays indicated that BBR mediated BNIP3 expression by enhancing the binding of HIF-1α to the BNIP3 promoter. BBR protects against myocardial I/R injury by inducing cardiomyocytes proliferation, inhibiting cardiomyocytes apoptosis, and inducing the mitophagy-mediated HIF-1α/BNIP3 pathway. Thus, BBR may serve as a novel therapeutic drug for myocardial I/R injury.